Nursing Student Freshers' Satisfaction of Orientation Education - Elyeli, Kemal; Bebis, Hatice (Galenos Publ House, 2022)
Objective: The aim of this study is to evaluate the satisfaction of the orientation program which is given to Near East University Faculty of Nursing's freshers. Methods: The freshers of the Near East University Faculty of Nursing (N N = 160) constitute the universe of the research, and the sample of the research consists of voluneteer students (n n = 140). Data were collected through a questionnaire survey form which is composed of 20 questions that include10 questions pertaining to sociodemographic characteristics and 10 questions pertaining to the orientation training satisfaction level. SPSS 21.0 statistical program was used for statistical analysis andthe data were shown as number, percentage, average, and standard deviation and evaluated by the chi-square test. Results: The average age of students was x = 19.7 +/- 1.9; the research comprises 41.4% of male students and 58.6% of girl students and 82.1% were seen coming from Turkey. About 89.0% of the girl students (n n = 73) indicated that generally orientation education (x2 x 2 = 6.313; p = . 012) was sufficient and 85.4% (n n = 70) of the girl students specified that Near East University promotion was successful. In addition, 81.7% of the male students (n n = 67) found the promotion of university facilities (x2 x 2 = 5.707; p = . 017) to be sufficient. Conclusion: In conclusion, it was determined that the students were highly satisfied with the orientation education and that this education should be continued in the coming years.
Keywords: Orientation training; nursing; university integration